Aprepitant and Fosaprepitant: A 10‐Year Review of Efficacy and Safety. (20th March 2015) - Aapro, Matti; Carides, Alexandra; Rapoport, Bernardo L.; Schmoll, Hans‐Joachim; Zhang, Li; Warr, David
Abstract : Chemotherapy‐induced nausea and vomiting (CINV) is a common adverse event associated with anticancer treatment that can have a significant adverse impact on patient health‐related quality of life and that can potentially undermine the effectiveness of chemotherapy. Traditional regimens to prevent CINV generally involved a combination of a corticosteroid plus a 5‐hydroxytryptamine (5HT3 ) receptor antagonist (RA). In the past 10 years, antiemetic treatment has greatly advanced with the availability of the neurokinin‐1 receptor antagonist (NK1 RA) aprepitant and its prodrug fosaprepitant. NK1 RAs have a different mechanism of action in CINV than corticosteroids and 5HT3 RAs, thus their use can complement traditional antiemetic drugs and can enhance control of CINV. This review examined accumulated data regarding the safety and efficacy of aprepitant and fosaprepitant over the decade since the first regulatory approval. Data from key studies of aprepitant and fosaprepitant in the prevention of CINV in patients receiving moderately and highly emetogenic chemotherapy were explored, as were recommendations in currently available guidelines for their use. In addition, their use as antiemetic therapy in special patient populations was highlighted. Future perspectives on potential uses of aprepitant and fosaprepitant for indications other than CINV are presented. Abstract : Aprepitant (and its prodrug fosaprepitant) is a neurokinin‐1 receptor antagonist approved more than a decade ago for the prevention of chemotherapy‐induced nausea and vomiting (CINV). This review examined safety and efficacy data for aprepitant and fosaprepitant and explored recommendations in current guidelines for their use. Future perspectives on potential uses of aprepitant and fosaprepitant for indications other than CINV are discussed.